Multilinear Commutators of $θ$-Type Calderόn-Zygmund Operators on Non-Homogeneous Metric Measure Spaces (Analysis in Theory and Applications, 2017)
In this paper, the boundedness in Lebesgue spaces of commutators and multilinear commutators generated by $θ$-type Calderόn-Zygmund operators with $RBMO(μ)$ functions on non-homogeneous metric measure spaces is obtained.
Keywords: Multilinear commutators; $θ$-type Calderόn-Zygmund operators; non-homogeneous metric measure spaces; $RBMO(μ)$.